Augmented Reality Reflections on its Contribution to Knowledge Formation - Ariso, José Maria (De Gruyter, 2017)
There is at present no publication specifically dedicated to analyzing the philosophical implications of augmented reality. Applications cover diverse fields like psychopathology and education, implications concern issues as diverse as negative knowledge, group cognition, the internet of things, and ontological issues, among others. In this way, it is intended not only to generate answers, but also, to draw attention to new problems that arise with the diffusion of augmented reality. In order to contemplate these problems from diverse perspectives, the authors are from a variety of fields - philosophy, computer sciences, education, psychology, and many more. Accordingly, the volume offers varied and interesting contributions which are of interest to professionals from multiple disciplines.